Beginners guide to circular dichroism. (12th April 2021) - Rodger, Alison; Marshall, Doug
Abstract : Circular dichroism (CD) is used to give information about the chirality or handedness of molecular systems. It is particularly widely applied to determine the secondary structure of proteins such as biopharmaceutical products.